Fast and Selective Adsorption of Au (III) from the Waste Printed Circuit Boards Using a Low-Cost Adsorbent: Optimization by Central Composite Design Based on Response Surface Methodology - Farideh Zandi-Darehgharibi; Hedayat Haddadi; Arash Asfaram (Journal of Chemistry)
A low-cost new green adsorbent (GA) was synthesized by tannin-rich pomegranate peel powder and formaldehyde for the fast and selective recovery of Au (III). It was characterized by Fourier transform infrared spectroscopy (FT-IR), Brunauer–Emmett–Teller (BET), elemental analysis (CHN), field emission scanning electron microscopy (FE-SEM), and energy-dispersive X-ray spectroscopy (EDS) (FE-SEM-EDS-mapping). The optimal values of influential factors were defined using a central composite design based on the response surface methodology (CCD-RSM). Adsorption properties were investigated by the kinetic, isotherm, thermodynamic, and interference of coexisting metal ions at optimum conditions. The experimental adsorption percentage with three repetitions under the optimized conditions such as pH = 2, adsorbent mass = 23 mg, Au (III) concentration = 32 mg L−1, and contact time = 30 min was 97% and the highest adsorption capacity of the GA was 315.450 mg g−1. The adsorption isotherm and kinetic were clarified by the Freundlich (R2 = 0.952) and pseudo-second-order (R2 = 0.998) models. The thermodynamic study (∆S° > 0, ∆H° > 0, and ∆G° < 0) revealed that Au (III) adsorption via GA was a facile, endothermic, and spontaneous process. The adsorption mechanism could be an electrostatic interaction and reductive adsorption. A small amount of GA (23 mg) adsorbed gold selectively and rapidly (30 min) from coexisting metals present in the waste printed circuit board (PCB) such as Ag, Al, Si, Zn, Pb, Ba, Ni, Ca, Mo, Co, Cr, Mn, Cu, Mg, Fe, and W. These results confirm the use of low-cost and high-efficiency GA to fast and selectively recover gold from waste PCBs.